(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This paper explores the semiotic dynamics of interface design in content platforms, taking a closer look at the cases of Netflix and Spotify. Digitization has placed the content platforms at the core of user experience in the contemporary media landscape, and it is imperative to understand the semiotic systems encoded in their interfaces for users and developers alike. The gap of the study, therefore, is based on how visual, auditory, and interactive elements encode meaning and influence user behavior for a deeper engagement in content on these platforms. This paper critically aims at examining how semiotic strategies in the interface designs of Netflix and Spotify shape users’ perceptions, choices, and interaction patterns that culminate in an overall experience. This research takes a semiotic eclectic approach—drawing on the core tenets of Roland Barthes’ structural semiotics (1960s), Charles Peirce’s semiotic theory (1930s), and Umberto Eco’s theories on the interpretation of signs (1970s), in combination with more recent developments in design semiotics (2010s). The dataset for this research comprises a collection of interface snapshots taken from both platforms. To analyze these, the design elements were considered, namely: layout, color schemes, iconography, typography, and sound. Specifically, it dwells on the use of visual metaphors, symbolic representation, and navigational cues in directing users through their processes of content discovery. Findings show how both Netflix and Spotify strongly feature elements that are not only highly personalized and symbolic in nature but also elicit emotional responses through their signifying practices. While both platforms follow a minimalist and user-centered design approach, the semiotic strategies behind them differ in that Spotify depends on audio-visual engagement, while Netflix leans towards visual storytelling and content curation strategies. The stakes are high with these design choices for how users will experience and engage with the content on the platforms. This research contributes to general knowledge of semiotic theory within digital design and its implications for user experience.